Cyberbullying via social media and well-being. (June 2022) - Giumetti, Gary W.; Kowalski, Robin M.
Abstract: In this article, we review research examining cyberbullying via social media among youth and adults and the relationship such behavior has with well-being. We report on several possible predictors of cyberbullying via social media, including indiscreet posting, time spent on social media, and personality traits. We also highlight possible negative effects on well-being that may be linked with cyberbullying via social media, including psychological distress, decreased life satisfaction, and suicidal ideation. We conclude the review with ideas for prevention and intervention, including the use of cyberbullying detection software to encourage users to think twice before posting a cyberbullying message. We also highlight several limitations with the existing research and provide some suggestions for future research opportunities.